Factors Affecting the Sleep Quality of Covid-19 Survivor: an Analysis in Kupang City, Eastern Indonesia - Sangguana Marthen Jacobus Koamesah; Idawati Trisno; Priska Deviani Pakan (Journal of Social Research, 2023)
With the success of COVID-19 vaccination program, number of COVID-19 survivors might increase significantly. Previous studies indicate that poor sleep quality might be one of the main problems experienced by COVID survivors that need to be addressed since it could disrupt immune system that help preventing re-infection or other health problems. This study examined factors associated with sleep quality of COVID-19 survivors at Kupang city, Eastern Indonesia. This is a cross-sectional survey, phone interviewed was used to collect data from COVID survivors regarding their perceived sleep quality using PSQI tools. Guided questionnaires used to collect information on demographic characteristics and COVID-19 infection characteristics. Multinomial logistic regression was conducted to test the proposed model of sleep quality predictors. Valid data of 148 COVID-19 survivors was collected in May to June 2021. The majority of participants were female (65.54%), aged between 21-50 years old (77.70%) and 12.16% were health workers. Most of participants were undergone self-isolation (79.73%), had no comorbidities (78.38%), had at least 3 organ systems affected during the infection (53.38%), had post COVID symptoms (58.78%), and 57.43% have poor sleep quality (PSQI score >5). The most common post COVID symptoms were fatigue (60.47%), followed by cough (25.58%), and joint/muscle pain (25.58%). The logistic regression model suggested prolonged hospitalization/self-isolation period more than 14 days and the presence of post COVID symptoms could predict higher risk of poor sleep quality. Additionally, higher number of organ systems affected during infection is increased the risk of having post COVID symptoms. Based on the findings of the factors affecting the sleep quality of COVID survivors, healthcare providers should concern sleep quality assessment as one of follow up protocols for COVID survivors, Health authorities should be aware of sleeping disorder as potential health problems in the future, thus a strategy to equip doctors in management of sleeping disorders should be considered, especially in the rural area of Eastern Indonesia.